Pengabdian Untuk Meningkatkan Motivasi Kemampuan Membaca Siswa SD Negeri Kapasan III Surabaya - Aprilia Tri Wahyuni; Endang Indartuti (Universitas Muhammadiyah Manado, 2023)
Lack of reading comprehension skills can make motivation low, indeed in spite of the fact that one of the vital viewpoints that must be aced in rudimentary school instruction is nice perusing abilities. This think about points to depict the increment in inspiration for perusing comprehension abilities with the BACA (Learning to Examined) program. The method of literature study as a source of information and direct observation and observation to the field. Activity planning and implementation of activities there are main things that must be fulfilled to encourage student motivation in reading, namely: introducing the letters of the alphabet to students, teaching the pronunciation of vowels, teaching patent sentences in the middle and at the end, etc. Increasing motivation for reading skills with the BACA program has a positive impact on homeroom teachers and student guardians as well as students who take part in the program because the teaching and learning process is fun and not boring. However, the main role to encourage and encourage children is parents, because parental encouragement makes children feel closer and guiding children in the learning process at home can create good communication between children and parents.